Design for Low Voltage DC Distribution Network Testbed - Park, Sung-Won; Cho, Jintae; Kim, Juyong; Son, Sung-Yong (International Journal of Engineering and Technology, 2018)
Background/Objectives: A low voltage DC(LVDC) distribution network is gaining popularity as the next generation distribution network. However, LVDC network test environments are limited.Methods/Statistical analysis: A full-scale environment for LVDC distribution network test is preferable to evaluate various operation characteristics. However, it has limitations in implementation cost and operation methodologies. In this study, a 48V DC-based down-scale LVDC distribution network testbed is developed to enable the reproduction and observation of various phenomena of DC distribution networks.Findings: The proposed testbed provides flexible configuration capability by introducing S-connector and T-connector modules that can be controlled remotely, and real-time monitoring functions by using a data acquisition system connected to the nodes. Each connector can measure voltage and current with up to 250 kHz sampling frequency. The frequency analysis is also supported based on the collected data to evaluate power quality and characteristics of the distribution network.Improvements/Applications: Complicated phenomena of DC distribution systems can be easily implemented using the developed LVDC distribution network testbed.Â